Florid cemento-osseous dysplasia presenting as bilateral mandibular swellings – report of a rare case (Bangladesh Journal of Medical Science, 2026)
Florid cemento-osseous dysplasia, a benign non neoplastic fibro-osseous lesion more commonly occurs in middle aged Asian females. Most of the reported cases were asymptomatic. We report a case occurring in a middle aged Asian male with bilateral mandibular swelling, which is a rare finding alongwith radiographic and histopathological diagnostic challenges.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S351-S354